Effects of Empowerment Programs on Knowledge in Glycemic Control, and Diabetes Prevention Behaviors of type II Pre-diabetes Person in Urban Area, Phayao Province - Kulnitichai, Waratya; Ratsakulwong, Kamoluk (Journal of The Royal Thai Army Nurses, 2021)
The quasi-experimental research design aimed to examine the effect of the empowerment program on knowledge and glycemic control of persons with pre-diabetes and preventive behaviors of on persons who risk type II diabetes mellitus in urban area, Phayao Province, applying Gibson conceptual framework consisting of this studied. The subjects were 20–59-year-olds with qualifications as specified. Data were collected between October and December 2019. The subjects were simple random sampling, equally to thirty persons in each group. The experimental group received nursing care by the empowerment program but control group receiving regular nursing care from the public health care teams. The research instrument consists of three parts: General data recording, Knowledge assessment questionnaires or diabetes control and diabetes prevention behaviors questionnaire, the Alpha Cronbach Coefficient of 0.89, data analyzed in general with descriptive statistics. Comparative analysis of knowledge scores about glycemic control and diabetes prevention behaviors within the groups before and after joining the empowerment program using dependent t test and analyzing between of variance in experimental and control groups using independent t test statistics. The results showed that empowerment programs for type II diabetes mellitus prevention in the experimental group had higher scores than before the experiment, both within the group and between groups. Statistical had significant level .05. The finding reflects that teams, health care workers and those responsible for pre-diabetes person should continuing to apply empowerment concepts to improve the effectiveness of diabetes prevention in the community.